CrSbSe3 nano material with multilevel structure as well as preparation method and application of CrSbSe3 nano material

The multi-stage structure CrSbSe3 nanomaterial was prepared by solvothermal method, which solved the problems of high energy consumption in the preparation process and uneven morphology of the products in the prior art, and achieved the effect of efficient photocatalytic degradation of pollutants.

CN119954108AActive Publication Date: 2025-05-09QUFU NORMAL UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510154416.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-12
Publication Date
2025-05-09
Estimated Expiration
2045-02-12

Smart Images

  • Figure CN119954108A_ABST
    Figure CN119954108A_ABST
Patent Text Reader

Abstract

The invention discloses a multilevel structure CrSbSe3 nano material and a preparation method and application thereof. The microstructure of the nano material is a flower-shaped multi-stage nano structure formed by self-assembly of nanosheets, and the crystal form of the nano material is an orthorhombic phase. The preparation method comprises the following steps: (1) selecting soluble substances of chromium, antimony and selenium as a chromium source, an antimony source and a selenium source respectively; (2) adding a chromium source and an antimony source into a reaction medium consisting of organic amine, oleic acid and octadecene, and heating and dissolving to obtain a solution A; and (3) heating and dissolving a selenium source in oleylamine to obtain a solution B, mixing the solution A and the solution B, and carrying out solvothermal reaction to obtain the multilevel structure CrSbSe3 nano material. The method disclosed by the invention is mild in reaction condition and simple in process, and the prepared CrSbSe3 is of a multi-stage nanostructure with high crystallinity and has excellent catalytic degradation capacity for environmental pollutants.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of multi-level structure nanomaterials, and in particular to a multi-level structure CrSbSe3 nanomaterial, a preparation method of the nanomaterial and an application of the nanomaterial as a photocatalytic material. Background Art

[0002] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.

[0003] In the process of storage and conversion of clean renewable energy, the structure of catalyst materials is a key factor affecting catalytic performance. Among many nanostructures, multi-level nanostructured materials are regarded as one of the ideal basic materials for improving catalytic performance and have received extensive attention. Among them, chromium-based bimetallic selenides have aroused great research enthusiasm in the fields of catalysis, photoelectric conversion, environmental pollutant purification, information processing and storage due to their diversity of crystal structure and elemental composition.

[0004] As a material with both ferromagnetic and semiconductor properties, CrSbSe3 has important application potential in logic operations, information processing and storage. At present, Guy Ouvrard reported that CrSbSe3 can be synthesized by mixing chromium powder, iron powder and selenium powder in a ratio of 1:1:3 through high-temperature solid-phase reaction, heating to 700℃ and reacting for 5 days. In addition, Xu Xiaohong and Mircea Dinca reported the synthesis of one-dimensional CrSbSe3 nanostructures using template method and exfoliation method respectively and explored their magnetic properties.

[0005] However, the above-mentioned high-temperature solid-phase reaction method not only requires high energy consumption and long time in the preparation of CrSbSe3, but also the synthesized products usually show the shortcomings of uncontrollable size and non-uniform morphology, which greatly affects or limits the performance and application of CrSbSe3. In addition, there are few reports on the preparation of multi-level structured CrSbSe3 nanomaterials and their performance research. The inventor believes that it is of great significance to explore CrSbSe3 nanomaterials with different structures and their applications in energy storage and conversion. Summary of the invention

[0006] In view of the above situation, the present invention aims to provide a multi-level structured CrSbSe3 nanomaterial. The nanomaterial prepared by the solvothermal method is a self-assembled multi-level structure, which has significant advantages as a photo-chemical energy conversion material. The present invention verifies the application of the synthesized multi-level structured CrSbSe3 as a photocatalytic material. The results show that the multi-level structured CrSbSe3 nanomaterial can effectively photocatalytically degrade the environmental pollutant methylene blue.

[0007] Based on the above technical effects, the present invention provides the following technical solutions: According to a first aspect of the present invention, a multi-level structured CrSbSe3 nanomaterial is provided, wherein the crystal structure of the nanomaterial is an orthorhombic phase.

[0008] The nanomaterial is a "flower-like" multi-level structure formed by self-assembly of a plurality of nanosheets extending outward from the center of a sphere. Furthermore, the thickness of the nanosheet is 10-30 nm, and the side length is 100-200 nm. The present invention prepares the nanomaterial by a solvent-thermal method. Based on the reaction medium provided by the present invention, similar effects can be achieved by replacing different precursor sources, and the nanomaterial has the advantages of good repeatability, simple preparation method, and cost-effectiveness.

[0009] Therefore, the second aspect of the present invention provides a method for synthesizing the CrSbSe3 nanomaterial according to the first aspect, comprising the following steps: The chromium source and the antimony source are added to a reaction medium composed of an organic amine, oleic acid and octadecene, and heated to dissolve to obtain a solution A; the selenium source is heated to dissolve in oleylamine to obtain a solution B, and the solution A and the solution B are mixed to undergo a solvent thermal reaction to obtain the product.

[0010] In the above preparation method, the chromium source, antimony source and selenium source should be substances that can be dissolved in the reaction medium, including corresponding organic and inorganic substances, and the molar ratio of Cr:Sb:Se is preferably 1:1:3~6.

[0011] More preferably, the chromium source is selected from one or a combination of chromium trichloride, chromium acetylacetonate or chromium acetate; the antimony source is selected from one or a combination of triphenylantimony, antimony trichloride, antimony acetate or antimony bromide; the selenium source is selected from one or more of diphenyl diselenide, dibenzyl diselenide, selenium dioxide or selenium powder.

[0012] In the above reaction medium, the organic amine is selected from one or more of oleylamine, hexadecylamine or octadecylamine, wherein the organic amine, oleic acid and octadecylene are mixed in a volume ratio of 5-8:1-2:1-3.

[0013] The preparation of the above-mentioned solution A is preferably carried out in a nitrogen or other inert gas atmosphere. After the chromium source and antimony source are added to the reaction medium, the reaction is heated to 100-180°C for 30-120 minutes with continuous stirring to dissolve the chromium source and antimony source and remove oxygen, moisture and low-boiling impurities in the reaction system.

[0014] In the preparation of the above-mentioned solution B, the preferred heating temperature is 70-250°C.

[0015] The parameters of the above-mentioned solvothermal reaction are as follows: the temperature of the solution is maintained between 280 and 350°C, and the reaction time is controlled between 5 and 180 minutes. After the solvothermal reaction is completed, the solid matter in the reaction system is separated and retained, and washed with an organic reagent to obtain the above-mentioned CrSbSe3 nanomaterial. The above-mentioned separation method can be centrifugation or filtration, and the organic reagent used for the above-mentioned washing is anhydrous ethanol and / or cyclohexane.

[0016] This "flower-like" CrSbSe3 nanomaterial prepared by the above method has not been reported in existing research. Through electron microscopy observation, the CrSbSe3 nanomaterial presents multiple nanosheets extending arbitrarily from the center of the sphere outward. This structure has significant advantages as a catalytic material: the sheet structure extending outward can capture, absorb irradiation from different directions, and reflect light, and has a better light absorption effect; the flower-like structure can provide a larger specific surface area and is not easy to stack or agglomerate; the intrinsic non-layered crystal structure provides more active sites for the catalytic reaction. The third aspect of the present invention provides the use of the CrSbSe3 nanomaterial described in the first aspect as a photocatalytic degradation of environmental pollutants.

[0017] The present invention uses the photodegradation of methylene blue as a model to verify the photocatalytic efficiency of the above-mentioned nanomaterial, that is, the nanomaterial is used as a photocatalytic degradation material for the degradation of dye pollutants in a water environment. The water environment is a natural environment such as a river, lake, sea, etc., and also includes industrial and domestic water such as drinking water and treated sewage. The dye is a dye that can be degraded under light conditions, including but not limited to methyl blue, methylene blue, and Sudan red; in one embodiment verified by the present invention, the dye is methylene blue.

[0018] Compared with the prior art, the present invention has the following beneficial effects: 1. The CrSbSe3 nanomaterial synthesized by the method of the present invention is an orthorhombic phase with high crystallinity and contains a two-dimensional polygonal sheet nanostructure. Furthermore, the two-dimensional sheet CrSbSe3 nanomaterial can self-assemble into a "flower-like" multi-level nanostructure.

[0019] 2. The multi-level CrSbSe3 nanostructure can absorb scattered or reflected incident light multiple times in terms of solar energy storage and conversion, thereby improving the light absorption capacity of the material.

[0020] 3. The multi-level CrSbSe3 nanostructure can provide a larger specific surface area and accelerate the transmission of substances and electrons in the catalytic reaction process in the field of catalytic applications. On the other hand, it can overcome the shortcomings of stacking or agglomeration between catalysts.

[0021] 4. As an intrinsic non-layered crystal structure, the orthorhombic phase CrSbSe3 has a "flower-like" multi-level nanostructure, which can provide abundant catalytic active sites due to the presence of dangling bonds on its surface. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.

[0023] Figure 1 is the X-ray diffraction pattern (XRD) of the nanomaterial described in Example 1.

[0024] Figure 2 is a scanning electron microscope (SEM) photograph of the nanomaterial described in Example 1.

[0025] Figure 3 It is the ultraviolet visible near infrared (UV-vis-NIR) absorption spectrum of the nanomaterial described in Example 1.

[0026] Figure 4 This is a curve chart of the photocatalytic degradation of methylene blue by the nanomaterial described in Example 1.

[0027] Figure 5 It is the X-ray diffraction pattern (XRD) of the nanomaterial described in Example 2.

[0028] Figure 6 This is a scanning electron microscope (SEM) photograph of the nanomaterial described in Example 3.

[0029] Figure 7 It is the X-ray diffraction pattern (XRD) of the nanomaterial described in Example 4. DETAILED DESCRIPTION

[0030] It should be noted that the following detailed descriptions are all illustrative and intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.

[0031] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit exemplary embodiments according to the present invention. As used herein, unless the context clearly indicates otherwise, the singular form is also intended to include the plural form. In addition, it should be understood that when the terms "comprising" and / or "including" are used in this specification, it indicates the presence of features, steps, operations, devices, components and / or combinations thereof.

[0032] In order to enable those skilled in the art to more clearly understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below in conjunction with specific embodiments.

[0033] Example 1 A multi-level structure CrSbSe3 nanomaterial, the preparation method of which comprises the following steps: (1) In a 100 ml three-necked flask, add 0.1 mmol of chromium acetylacetonate, 0.1 mmol of triphenyl antimony, 8.0 ml of oleylamine, 1.0 ml of oleic acid and 1.0 ml of octadecene. Then, introduce nitrogen and heat the mixture to 130°C under magnetic stirring for 60 min to obtain solution A.

[0034] (2) In a 10 ml test tube, add 0.3 mmol of diphenyl diselenide and 1.0 ml of oleylamine respectively, and dissolve the diphenyl diselenide in oleylamine under ultrasonication and heating to 90°C to obtain solution B.

[0035] (3) When solution A is heated to 320°C, 1.0 ml of solution B is quickly injected into solution A, and the reaction is continued at 320°C for 120 minutes. After the reaction is completed, the solution is cooled to room temperature. Then, the solid product is washed and centrifuged three times with a mixture of anhydrous ethanol and cyclohexane in a volume ratio of 3:1 to obtain a solid product, namely the nanomaterial.

[0036] Example 2 A preparation method of a multi-level structure CrSbSe3 nanomaterial comprises the following steps: (1) In a 100 ml three-necked flask, add 0.1 mmol of chromium acetylacetonate, 0.1 mmol of antimony acetate, 7.0 ml of oleylamine, 1.0 ml of oleic acid, and 2.0 ml of octadecene. Then, introduce nitrogen gas and heat the mixture to 160°C under magnetic stirring and keep the reaction at this temperature for 30 min to obtain solution A.

[0037] (2) In a 10 ml test tube, add 0.3 mmol of diphenyl diselenide and 1.0 ml of oleylamine respectively, and dissolve the diphenyl diselenide in oleylamine under ultrasonication and heating to 90°C to obtain solution B.

[0038] (3) When solution A is heated to 300°C, 1.0 ml of solution B is quickly injected into solution A, and the reaction is continued at 300°C for 120 minutes. After the reaction is completed, the solution is cooled to room temperature. Then, the solid product is washed and centrifuged three times with a mixture of anhydrous ethanol and cyclohexane in a volume ratio of 3:1 to obtain a solid product, which is the target product.

[0039] Example 3 A preparation method of a multi-level structure CrSbSe3 nanomaterial comprises the following steps: (1) In a 100 ml three-necked flask, add 0.1 mmol chromium trichloride, 0.1 mmol antimony acetate, 5.0 ml oleylamine, 2.0 ml oleic acid and 3.0 ml octadecene. Then, introduce nitrogen and heat the mixture to 160°C under magnetic stirring and keep the reaction at this temperature for 30 min to obtain solution A.

[0040] (2) In a 100 ml three-necked flask, add 3 mmol of selenium powder and 10 ml of oleylamine. Ultrasonicate and then heat to 250°C to dissolve the selenium powder in the oleylamine to obtain solution B.

[0041] (3) When solution A is heated to 350°C, 1.0 ml of solution B is quickly injected into solution A, and the reaction is continued at 350°C for 30 minutes. After the reaction is completed, the solution is cooled to room temperature. Then, the solid product is washed and centrifuged three times with a mixture of anhydrous ethanol and cyclohexane in a volume ratio of 3:1. The solid product obtained is the target product.

[0042] Example 4 A preparation method of a multi-level structure CrSbSe3 nanomaterial comprises the following steps: (1) In a 100 ml three-necked flask, add 0.1 mmol chromium acetate, 0.1 mmol antimony acetate, 8.0 ml oleylamine, 1.0 ml oleic acid and 1.0 ml octadecene. Then, introduce nitrogen and heat the mixture to 110°C under magnetic stirring for 120 min to obtain solution A.

[0043] (2) In a 10 ml test tube, add 0.3 mmol of dibenzyl diselenide and 1.0 ml of oleylamine, respectively. Under ultrasonication and heating to 70°C, dissolve diphenyl diselenide in oleylamine to obtain solution B.

[0044] (3) When solution A is heated to 290°C, 1.0 ml of solution B is quickly injected into solution A, and the reaction is continued at 290°C for 180 min. After the reaction is completed, the solution is cooled to room temperature. Then, the solid product is washed and centrifuged three times with a mixture of anhydrous ethanol and cyclohexane in a volume ratio of 3:1. The solid product obtained is the target product.

[0045] Morphological characterization Figure 1 , Figure 5 and Figure 7 They are the X-ray diffraction results of the CrSbSe3 nanomaterials described in Example 1, Example 2 and Example 4 respectively. Figure 1The diffraction peaks in the middle all indicate the corresponding crystal planes in CrSbSe3 (JCPDS Card No. 88-0566) well, and no other impurity peaks appear, indicating that the nanomaterial prepared in Example 1 is an orthorhombic phase CrSbSe3 crystal. Figure 5 , Figure 7 The results show that the nanomaterials prepared in Example 2 and Example 4 have substantially the same diffraction peaks as Example 1, proving that a CrSbSe3 crystal is obtained in all of the above examples.

[0046] Figure 2 and Figure 6 The following are scanning electron microscope (SEM) photos of the nanomaterials obtained in Example 1 and Example 3, respectively. Figure 2 It can be seen that the CrSbSe3 prepared in Example 1 is a nanomaterial with a sheet structure, with a thickness of about 10-30 nm and a side length of about 100-200 nm. Figure 6 The results also show that the nanomaterial prepared in Example 3 has Figure 2 Similar results. In addition, the Figure 2 and Figure 6 The results also show that the nanomaterial provided by the present invention is a multi-level structure formed by self-assembly of several two-dimensional nanosheets. As shown in the figure, the multi-level structure refers to a multi-level structure similar to a "nanoflower" formed by cross-self-assembly of multiple sheets.

[0047] Performance Testing Figure 3 This is the ultraviolet visible near infrared (UV-vis-NIR) absorption spectrum of the nanomaterial in Example 1, which proves that the multi-level structure CrSbSe3 nanomaterial has a strong absorption capacity in the visible-near infrared light range, indicating that the multi-level structure CrSbSe3 nanomaterial can be used as a light-absorbing material in research fields such as photocatalysis and photoelectric conversion.

[0048] Figure 4 The photocatalytic degradation result of methylene blue by the nanomaterial described in Example 1. First, the multi-level structure CrSbSe3 nanomaterial was dispersed in a mixed solution of 4 mL cyclohexane and 1 mL mercaptopropionic acid under ultrasound, left to stand for 24 hours, and then washed by centrifugation with anhydrous ethanol three times for surface modification to enhance its water solubility. Secondly, 50 mg of the target product was weighed and dispersed into 50 mL of a 10 mg / L methylene blue aqueous solution, and stirred for 30 minutes in a dark place to reach adsorption / desorption equilibrium. Then, a 300 W xenon lamp was used for irradiation, and 1.0 mL of the mixed solution was centrifuged every 15 minutes. The supernatant was taken, and the absorbance at a wavelength of 664 nm was measured using a UV-visible spectrophotometer to calculate the degradation rate. Figure 4As shown, the hierarchical structured CrSbSe3 nanomaterials have good degradation ability for methylene blue dye.

[0049] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A multi-level structure CrSbSe3 nanomaterial, the crystal structure of the nanomaterial is an orthorhombic phase, the nanomaterial is a "flower-shaped" multi-level structure formed by self-assembly of a plurality of nanosheets extending outward from the center of a sphere, the thickness of the nanosheet is 10-30nm, and the side length is 100-200nm.

2. The method for preparing the CrSbSe3 nanomaterial according to claim 1, characterized in that: The steps include: The chromium source and the antimony source are added to a reaction medium composed of an organic amine, oleic acid and octadecene, and heated to dissolve to obtain a solution A; the selenium source is heated to dissolve in oleylamine to obtain a solution B, and the solution A and the solution B are mixed to undergo a solvent thermal reaction to obtain the product.

3. The preparation method according to claim 2, characterized in that: The chromium source, antimony source and selenium source are substances that can be dissolved in the reaction medium, including corresponding organic and inorganic substances, and the molar ratio of Cr:Sb:Se is preferably 1:1:3-6.

4. The preparation method according to claim 3, characterized in that: The chromium source is selected from one or a combination of chromium trichloride, chromium acetylacetonate or chromium acetate; the antimony source is selected from one or a combination of triphenylantimony, antimony trichloride, antimony acetate or antimony bromide; the selenium source is selected from one or more of diphenyl diselenide, dibenzyl diselenide, selenium dioxide or selenium powder.

5. The preparation method according to claim 2, characterized in that: The organic amine is selected from one or more of oleylamine, hexadecylamine and octadecylamine, wherein the organic amine, oleic acid and octadecene are mixed in a volume ratio of 5-8:1-2:1-3.

6. The preparation method according to claim 2, characterized in that: The preparation of the A solution is carried out in a nitrogen or other inert gas atmosphere. After the chromium source and antimony source are added to the reaction medium, the reaction is heated to 100-180° C. for 30-120 min with continuous stirring to dissolve the chromium source and antimony source and remove oxygen, moisture and low-boiling impurities in the reaction system.

7. The preparation method according to claim 2, characterized in that: In the preparation of the B solution, the heating temperature is 70-250°C.

8. The preparation method according to claim 2, characterized in that: The parameters of the solvothermal reaction are as follows: the temperature of the solution is maintained between 280 and 350°C, and the reaction time is controlled between 5 and 180 minutes. After the solvothermal reaction is completed, the solid matter in the reaction system is separated and retained, and washed with an organic reagent to obtain the CrSbSe3 nanomaterial according to claim 1.

9. Use of the CrSbSe3 nanomaterial according to claim 1 as a photocatalytic degradation material.

10. The use according to claim 9, characterized in that In the application, the nanomaterial is used as a photocatalytic degradation material for the degradation of dye pollutants in a water environment, wherein the water environment includes a natural environment as well as industrial and domestic water. The dye is a dye that can be degraded under light conditions, including but not limited to methyl blue, methylene blue, and Sudan red. In one embodiment verified by the present invention, the dye is methylene blue.

Citation Information

Patent Citations

  • Two-dimensional non-layered CuGaSe2 porous nanomaterial as well as preparation method and application thereof

    CN113683060A

  • Sulfide composite material for metal-ion battery, preparation method therefor, and application thereof

    WO2023087148A1